Pembuatan e-Portfolio Guru Peserta Program Yayasan Trampil Indonesia - Agnes Yustivani De Sirat; Adi Wibowo; Justinus Andjarwirawan (Jurnal Infra, 2015)
The development of education quaility in Indonesia can be done by improving the teachers’ quality. This development can be implemented through a certain regulation about teachers’ functional position and credit points’ system. Actually, this regulation is based on “Peraturan Menteri Pendidikan Nasional Nomor 35 Tahun 2010” which is talked about teachers’ functional position and the system of credit points. Yayasan Trampil Indonesia deeply supports that regulations by creating a functional training for teachers and having two supporting systems, namely e-admin and moodle.The difficult calculating system for credit points gives some problems to the teachers. That is why, teachers are not really focus in improving the education quality because they are too busy only in calculating the credit points. Therefore, we need a system to help the teachers in calculating the credit points.The system called e-portfolio. It will be connected with moodle and e-admin in order to calculate the credit points automatically. This connection uses the RESTfull web service. From the results of the questionnaire stated that this system help teachers to calculating the credit points. Indeed, this e-portfolio teachers can concentrate to improving the quality of education.